PROSES PEMECAHAN MASALAH MATEMATIKA PADA MATERI SPLTV DITINJAU DARI TIPE KEPRIBADIAN - Adityaningrum, Sitaresmi; Nurul Iffah, Jauhara Dian; Maf’ulah, Syarifatul (Dharmas Education Journal (DE_Journal), 2024)
The important position of problem solving in mathematics learning requires teachers to provide opportunities for learners to solve problems. The process of solving problems based on John Dewey's steps is certainly not all students can solve them appropriately. This is due to the differences in behavior / personality of each individual in solving problems. This study aims to describe the process of solving students' mathematical problems based on personality type. This research is a qualitative research with a descriptive method. The subjects of the study were taken from class X TKJ 1 SMKN Gudo. Data collection was carried out by the method of problem-solving tests and interviews. Checking the validity of the data is carried out by triangulation of time. Teknik analisis data dilakukan dengan reduksi dan penyajian data serta penarikan kesimpulan. The results of this study reveal the process of solving mathematical problems with John Dewey's steps, including: recognizing problems, defining problems, formulating hypotheses, collecting and grouping data as material for proving hypotheses, and choosing the best hypotheses with personality types according to David Keirsey, namely guardian, artisan, rational, and idealist. At the stage of recognizing the problem the type of personality that retells a given problem is rational even though the subject re-reads the given problem. The stage of defining the problem of personality types that meet the indicators is guardian, rational and idealist that is to write down what is known and what is asked. The stage of formulating a hypothesis there is no personality type that meets the indicators, all subjects do not make plans but make problem-solving measures. The stage of collecting and grouping data as a material for proving the hypothesis of all personality types does the same thing that is to solve the problem according to the plan made. At the stage of choosing the best hypothesis with the indicator of retelling the step of its answer that meets the indicator is an idealist personality type, in addition to retelling the answer this subject also writes down other ways and proofs to know if the answer is true or false.